IMPLEMENTATION OF MUDHARABAH AGREEMENT IN TABAH PRODUCTS WITHIN THE FRAMEWORK OF ISLAMIC PRINCIPLES OF JUSTICE AND ECONOMIC PROFIT SHARING AT BMT NU PURWOHARJO BRANCH, BANYUWANGI - Azzahra, Amelia; Ustanti, Mira (Universitas Islam Negeri Mataram, 2025)
This research aims to comprehensively analyze the implementation of the mudharabah contract in TABAH savings products at BMT NU Purwoharjo Branch, focusing on its conformity with Islamic economic principles. The novelty of this study lies in its contextual exploration of the Purwoharjo Branch, which has unique socio-economic characteristics, and in offering an operational assessment of mudharabah practices that have not been covered in previous research. The study also critically examines how operational standards reflect Islamic values such as justice, amanah (trust), and maslahah (public benefit). This research uses a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with BMT managers and customers, direct observations of daily operations, and analysis of documents such as SOPs, financial reports, and contract agreements. Data validation was ensured through source, method, and theoretical triangulation, and analysis was conducted using Miles and Huberman's interactive model involving data reduction, categorization, and conclusion drawing. The findings show that implementing the mudharabah contract at BMT NU Purwoharjo Branch aligns with key Islamic economic principles such as transparency, fairness in profit-sharing, and trust-based (amanah) fund management. The profit-sharing ratio is determined based on mutual agreement, reflecting Islamic law's principle of willingness (taradhi). However, a gap remains in customer understanding of mudharabah mechanisms, particularly regarding the concept of risk-sharing and the customer's role as shahibul mal, indicating the need for strengthened financial literacy. On the other hand, BMT's fund allocation supports halal and productive micro-business sectors, aligning with the principle of maslahah and contributing to local economic empowerment. Risk mitigation is addressed through stringent partner selection and continuous monitoring. This study provides practical insights into operationalizing Islamic contractual values in microfinance institutions and expands the growing literature on context-based mudharabah implementation.